Enhanced thermal stabilization and reduced color formation of plasticized Poly(vinyl chloride) using zinc and calcium salts of 11-maleimideoundecanoic acid. (January 2015) - Mohammed, Fiaz S.; Conley, Mark; Rumple, Amber C.; Saunders, Steven R.; Switzer, Jackson; Urena-Benavides, Esteban; Jha, Rani; Cogen, Jeffrey M.; Chaudhary, Bharat I.; Pollet, Pamela; Eckert, Charles A.; Liotta, Charles L.
Abstract: Above certain temperatures, untreated PVC undergoes dehydrochlorination to produce conjugated polyenes in the polymer backbone. This is accompanied by formation of color in the polymer. In order to address both the thermally induced dehydrochlorination process and the accompanying color formation the dienophilic zinc and calcium salts of 11-maleimidoundecanoic acid (Zn11M and Ca11M, respectively) were synthesized and employed as stabilizing additives. The stabilizing effect of the Zn11M and Ca11M on PVC was studied at 170 °C in air. Evidence is presented which shows that this combination of salts performs a dual role of reducing both the rates of dehydrochlorination and formation of color in plasticized PVC.